Z-MART BAZNAS PROGRAM IN IMPROVING MUSTAHIK'S ECONOMIC WELFARE - Anisa; Sayuti , Muhammad Noor; Hanafi , Ahmad (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2024)
This research aims to examine and analyze the management of the Z-Mart program in improving the economic welfare of mustahik in BAZNAS, South Kalimantan Province. As well as analyzing the obstacles in implementing the Z-Mart program in improving the economic welfare of mustahik in BAZNAS South Kalimantan Province. This research uses field research with a qualitative approach. The research location is at BAZNAS, South Kalimantan Province. The subjects of this research were the Zakat utilization team and mustahik recipients of the Z-Mart program as informants. Data collection methods used include observation, interviews and documentation. Data validation was carried out through source triangulation and data analysis involving the stages of collection, reduction, presentation and concluding. The research results show that Z-Mart management includes five main aspects: namely planning, organizing, movement or implementation, monitoring and evaluation. BAZNAS South Kalimantan Province succeeded in managing the Z-Mart program without significant obstacles thanks to good management, careful planning, effective organization, comprehensive training and strict supervision. With this approach, every aspect of the program is managed optimally so that the program objectives carried out by BAZNAS South Kalimantan Province are planned and realized well and systematically.